THE SYNERGY OF RHETORIC AND PUBLIC SPEAKING IN CONTEMPORARY ISLAMIC DA'WAH - Mia Fitriah Elkarimah (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
da'wah, arguing that mastery of both competencies is essential for effective, ethical, and impactful religious communication. This research is a literature study employing a qualitative approach through conceptual analysis, drawing exclusively on primary and secondary written sources, including classical rhetorical texts, Qur'anic foundations, and peer-reviewed journal articles, rather than on field observation or empirical data collection. This methodological position was deliberately chosen to enable theoretical synthesis across classical rhetoric, Islamic communication studies, and digital media scholarship. The study integrates classical rhetorical principles, logos, ethos, and pathos with the Islamic communicative foundations of hikmah, mau'izhah hasanah, and jidal bil-latif as articulated in Surah An-Nahl (16:125). The central argument is that rhetoric functions as